1993
DOI: 10.1212/wnl.43.12.2484
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR spectroscopic characterization of differences in regional brain metabolic abnormalities in mitochondrial encephalomyopathies

Abstract: Localized brain proton MR spectra were acquired from patients with different mitochondrial encephalomyopathies (myoclonus epilepsy with ragged-red fibers [MERRF], Kearns-Sayre syndrome [KSS], and mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes [MELAS]). The regional brain metabolic abnormalities in patients with these syndromes showed different features consistent with the distinct phenotypes. In MERRF, only one of four patients showed an increase in the lactate/creatine resonance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 0 publications
2
69
2
4
Order By: Relevance
“…54 As a result, elevated lactate levels are commonly used to diagnose and confirm mitochondrial disorders, particularly those that affect the central nervous system. 16,[55][56][57] Additionally, animal studies have confirmed that significant increases in brain lactate, as well as decreases in pHi, occur as a result of induced, isolated mitochondrial failure. 58 In one study, in which Clausen et al 58 used cyanide to induce mitochondrial failure in the feline brain, an analysis of corresponding extracellular lactate concentrations and brain tissue pH suggests a logarithmic relationship between the two measure-…”
Section: Elevated Lactate In Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…54 As a result, elevated lactate levels are commonly used to diagnose and confirm mitochondrial disorders, particularly those that affect the central nervous system. 16,[55][56][57] Additionally, animal studies have confirmed that significant increases in brain lactate, as well as decreases in pHi, occur as a result of induced, isolated mitochondrial failure. 58 In one study, in which Clausen et al 58 used cyanide to induce mitochondrial failure in the feline brain, an analysis of corresponding extracellular lactate concentrations and brain tissue pH suggests a logarithmic relationship between the two measure-…”
Section: Elevated Lactate In Bipolar Disordermentioning
confidence: 99%
“…13,14 In fact, research on cerebral injury by Demougeot et al 15 has indicated that cellular dysfunction can actually cause greater measurable reductions in NAA than neuronal loss. Abnormally low ratios of NAA/Cr þ PCr have been observed in patients with a number of mitochondrial encephalomyopathies, 16 and studies using mitochondrial respiratory chain inhibitors have also shown that reductions in NAA are correlated with decreases in O 2 consumption and ATP production. 7,14,17 When taken together, these studies suggest that NAA levels are closely related to mitochondrial energy metabolism, and thus may serve as a measure of mitochondrial function.…”
mentioning
confidence: 99%
“…To our knowledge, MRS findings in the brain of patients with mitochondrial disorders have been reported only in individual cases or small series, and most studies were carried out in areas of the brain that appeared abnormal on magnetic resonance imaging (MRI) as part of the clinical investigation of the patient. [7][8][9][10][11][12][13][14][15] The most consistent findings have been higher lactate levels and lower N-acetyl-aspartate levels, although lower creatine and glutamate levels, and altered levels of choline have also been reported. [7][8][9][10][11][12][13][14][15] In this study, we measured metabolites in vivo in patients with mitochondrial disorders compared with age-and sexmatched healthy controls using standardized voxel placement in 3 brain regions commonly implicated in neuropsychiatric disorders: the caudate nucleus, anterior cingulate cortex and hippocampus.…”
Section: Cmaj Openmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] The most consistent findings have been higher lactate levels and lower N-acetyl-aspartate levels, although lower creatine and glutamate levels, and altered levels of choline have also been reported. [7][8][9][10][11][12][13][14][15] In this study, we measured metabolites in vivo in patients with mitochondrial disorders compared with age-and sexmatched healthy controls using standardized voxel placement in 3 brain regions commonly implicated in neuropsychiatric disorders: the caudate nucleus, anterior cingulate cortex and hippocampus. [16][17][18][19] Our primary hypothesis was that patients with mitochondrial disorders would have reduced levels of markers of mitochondrial dysfunction (N-acetyl-aspartate and creatine) compared with healthy controls in the 3 candidate brain regions.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Possibly, our Patients 2 and 3 had a more severe form of the disease with a massive increase of glycolysis that could not be maintained for a long time. Theoretically, massive lactate accumulation could exert toxic effects [28] and thus contribute to the unfortu nate outcome; but increased cerebral lactate signals have also been described in chronic cases of mitochon drial encephalomyopathies [29].…”
Section: 75000mentioning
confidence: 99%